Falling together : a family's story of mental illness and grief - Sharkey, Donna (Demeter Press, 2021)
The author anticipated building an ordinary family. And that's what happened. But mental illness and grief also happened, undermining the security of home and changing the familial experience from ordinary to extraordinary. A hard story to live, a hard story to read, this book describes the day to day life in a family navigating their increasingly fraught lives. A must read for any family who has experienced this and a must read for anyone wanting to know about this.